1989
DOI: 10.1118/1.596383
|View full text |Cite
|
Sign up to set email alerts
|

The use of storage phosphors for portal imaging in radiation therapy: Therapists' perception of image quality

Abstract: Two drawbacks in quality of portal radiographs in radiation therapy are their low contrast and low spatial resolution. These are due to the low differential absorption of body tissues at therapeutic energies and to a relatively large radiation source. We used an experimental, high-contrast sensitivity storage phosphor imaging system (Eastman Kodak Co.) to produce portal images. The system consists of a storage phosphor detector, a high-contrast sensitivity laser scanner (12 bit), an image processing module, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 0 publications
0
14
1
Order By: Relevance
“…Since it has been shown in this and other studies 5 , 6 that CR may also be used to acquire portal images for verification of treatment setup, one may conclude that digital acquisition of treatment portal images makes it possible for a radiation oncology department to establish a PACs that incorporates both treatment planning and setup verification images.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Since it has been shown in this and other studies 5 , 6 that CR may also be used to acquire portal images for verification of treatment setup, one may conclude that digital acquisition of treatment portal images makes it possible for a radiation oncology department to establish a PACs that incorporates both treatment planning and setup verification images.…”
Section: Discussionmentioning
confidence: 73%
“…CR, on the other hand, can be used to acquire images with wide exposure latitude, spatial resolution equivalent to that obtained with portal films and low noise. It was previously demonstrated that computer enhanced contrast of portal film images 21 and CR portal images 5 significantly improved visualization of anatomical structures in portal images. The present study, however, did not make a comparison between histogram‐equalized CR and digitized portal film images.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High contrast resolution improves the physician's ability to delineate anatomical landmarks with respect to beam placement. 11,12 As discussed in the previous section, contrast resolution in megavoltage images is severely limited due to the dominance of Compton interactions at these high x-ray energies.…”
Section: Requirements Of a Portal Imaging Systemmentioning
confidence: 99%
“…Dosimetric verification is performed by measuring the dose at some points inside or outside the patient and comparing the measured values with theoretically calculated dose values at the same points. 3 Verification of geometric localization is performed by imaging the patient before or during the treatment and comparing 12 these images with simulation images. The acquisition of megavoltage x-ray images through the treatment portal of the therapy unit is known as portal imaging.…”
Section: Verificationmentioning
confidence: 99%